Analisis Pertimbangan Hakim di Pengadilan Agama Mungkid Terkait Tidak Diterimanya Izin Poligami yang Terpenuhinya Syarat Kumulatif (No.296/Pdt.G/2021/PA.Mkd): Analysis of Judges' Considerations at the Mungkid Religious Court Regarding the Non-Acceptance of Polygamy Permits That Meet the Cumulative Requirements (No.296/Pdt.G/2021/PA.Mkd) - Andra Nugraha; Ali Akbar (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This study aims to analyze the judge's considerations in the case of a polygamy permit application at the Mungkid Religious Court registered with Number 296/Pdt.G/2021/PA.Mkd, where the application was rejected even though the applicant had met the cumulative requirements as stipulated in Articles 4 and 5 of Law Number 1 of 1974 concerning Marriage. The approach used is normative juridical and sociological juridical, with data collection techniques in the form of studying court decision documents and interviews with related parties. The results of the study show that judges do not only consider the fulfillment of formal and material requirements, but also consider aspects of substantive justice, family welfare, and the potential for harm in the future. This decision reflects the judge's authority to interpret legal norms progressively for the protection of the rights of wives and children, as well as a form of judicial control over polygamy practices that have the potential to harm certain parties. Thus, this study contributes to a deeper understanding of the judge's discretion in deciding polygamy cases which is not only oriented towards fulfilling written norms, but also on the principles of justice and protection of the weaker party.